Pemberdayaan dan Peningkatan Ekonomi Keluarga Kelompok Tani Kampung Sakui-Kui dengan Menciptakan Produk Ekonomi Kreatif Berbahan Dasar Tanaman Jagung: Pengabdian - Elpisah; Sumarwadji, Hafid; Andi Tonra Lipu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aims to increase the economic value of corn in Kampung Sakui-Kui by empowering youth members of Karang Taruna as the main partners in developing creative economic products made from corn. Although the area has abundant corn production potential, its contribution to household income remains low because most harvests are sold in raw form without any added-value processing. To address this issue, the program was implemented through a series of technical trainings on corn processing, production assistance, and capacity building in business management and marketing. This initiative resulted in the creation of value-added corn-based products, particularly corn marning, which offer greater market opportunities. The outcomes show significant improvements in production skills, increased motivation and entrepreneurial awareness among Karang Taruna youth, and emerging potential for enhancing family income through diversified corn-based products. Overall, this program has the potential to serve as a sustainable model for rural creative economic empowerment through the optimization of local agricultural commodities